Disséminer sa recherche dans l’espace public numérique : notes d’un chercheur connecté - Mathieu Jacomy (Tracés, 2021)
Social media provides a way for researchers to know their audience, albeit imperfectly; This is one of the benefits of opening an online research blog or a Twitter account. From my own experience of disseminating knowledge on Twitter and writing a research blog on Hypotheses.org, I paint a portrait of the digital public space, as it appears to me in this context, drawing inspiration on Franck Ghitalla’s work about the web. I use network analysis as a conceptual framework to give a representation of the web’s structure in vertically stacked layers of visibility. This model allows me to ask the question of our situation on the web when we try, as researchers, to engage in a dialogue with an online audience without aiming for the maximum visibility that characterizes the figure of the influencer. I conclude that, even though researchers do not have the same goals as influencers, they may derive modest benefits from the digital traces returned by platforms.